An Irradiance‐Adaptable Near‐Infrared Vertical Heterojunction Phototransistor. Issue 40 (4th September 2022) - Zhang, Mengyu; Chi, Zhiguo; Wang, Guoqing; Fan, Zelong; Wu, Honglei; Yang, Ping; Yang, Junbo; Yan, Peiguang; Sun, Zhenhua
Abstract: Bioinspired artificial visual perception devices with the optical environment‐adaptable function have attracted significant attention for their promising potential in applications like robotics and machine vision. In this regard, a photodetector with in‐sensor adaptability is longed for in terms of complexity, efficiency, and cost. Here, a near‐infrared phototransistor with a benign light irradiance‐adaptability is presented. The phototransistor uses a vertically stacking graphene/lead sulfide quantum dots/graphene heterojunction as the conductive channel. Compared with ordinary lead sulfide quantum dots‐decorated graphene phototransistors, the present device demonstrates a faster photoresponse speed and an abnormal transfer characteristic. The latter characteristic is induced by the gate voltage‐tunable Fermi level in the heterojunction and the abundant electron trap states in the quantum dot film, which jointly results in an intense dependence of the photoresponse on the gate voltage. The dynamic trapping and de‐trapping processes in the quantum dot film enable the inhibition or potentiation of the photoresponse, based on which the photopic or scotopic adaptation behavior of the human retina is successfully mimicked, respectively. By providing an irradiance‐adaptable photodetector with a spectral response beyond visible light, this work should inspire future research on artificial environment‐adaptable perception devices. Abstract : A near‐infrared phototransistor using the graphene/lead sulfide quantum dots/graphene heterojunction as the conductive channel is fabricated. The device demonstrates an intense gate voltage‐dependent photoresponse. The dynamic trapping and de‐trapping processes in the quantum dot film enable the inhibition or potentiation of the photoresponse, based on which the photopic or scotopic adaptation behavior of the human retina is successfully mimicked, respectively.